PENGARUH GUIDED DISCOVERY LEARNING TERHADAP AKTIVITAS BELAJAR GEOGRAFI SISWA KELAS X DI SMA PUSRI PALEMBANG - yuni yuni; edi harapan; Nuranisa Nuranisa (Geography Education Study Program, Faculty of Teacher Training and Education, 2021)
ABSTRACT This study aims to increase the influence of the guided discovery discovery method on the learning activities of class X geography students at Pursi Palembang High School. The research method used is a quantitative approach using experiments with data collection techniques using observation sheets. The population in this study was class X Palembang Pusri High School, the sampling was obtained from class ips1 as the experimental class and class X ips2 as the control class. Data analysis techniques based on calculations, obtained t count> t table = 0.45> 1.34, namely t count = 0.45 and t table = 1.34 then accept the hypothesis (ha) which means